Presentation of the model of financing of small and medium- sized enterprises according to the French and Algerian experience - Abdelkader, Slim Bourchid; Mousa, Elsiddig Yousif Mohammed; Hamidouche, Mohamed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to present the method of financing small and medium enterprises, by comparing the French model with the Algerian model, the researcher used the descriptive analytical method to address the study variables and to present the study’s axes. The researcher has reached several results, the most important of which is the presence of similarities in the experiences of some countries in monitoring financial resources in the form of public savings intended for the financing of small and medium enterprises, and they differ in the banking system specialized in financing small and medium enterprises. The French experience is unique in consolidating these financial resources resulting from the savings of families and organizations within a special system directed to the benefit of small and medium enterprises development bank. Based on the results obtained, the researcher presented a set of recommendation, the most important of which is the need to take into account all internal and external variables when designing financing models for small and medium enterprises, in order to ensure the provision of appropriate financing, in the right size and at the right time, in order to ensure the growth and continuity of these institutions.